Efficiency of Steel Fiber on Carrying Capacity of Short Square Columns - Haider Abdulridha Alkufi; Mohannad Husain Al-Sherrawi (Civil Engineering Journal, 2018)
An experimental investigation is carried out to find the beneficial effect of adding steel fiber to reinforced concrete square columns. Hooked end steel fiber type is used in this investigation. The aspect ratio is 60 and the percentages of the steel fiber that added to the concrete are 0.5%, 1.0% and 1.5%. The experimental work consists of fabricated twenty columns to observe the effect of steel fibers on the axial and bending moment capacity. The specimens are classified into five groups according to the applied load on it. Each of these groups is consisted of four columns having different steel fiber ratios (0, 0.5, 1.0 and 1.5) %. The columns are tested under concentric, eccentric with variable eccentricities and two-point loading. All tested columns in a one group having the same dimensions, same interior reinforcement and were tested under one applying–load and they have a square cross-section with a dimension of (100 × 100) mm. Specimens with steel fiber results are compared with the control specimen of their own (columns mad of plain concrete). The results showed that increasing steel fiber ratio is caused an increasing in the first cracking load and an increase in the ultimate load for all tested columns.